Synthesis of bismuth vanadate and copper-doped bismuth vanadate as visible light photocatalysts - Mohd Ali, Norsalinda (2010)
Since the majority of sunlight consists of visible light and only 3-5% of UV light,numerous studies has been pointed out to develop an alternative semiconductor that have higher efficiency on visible light irradiation. Visible light induced BiVO4 photocatalyst with monoclinic structure has been successfully synthesized via precipitation method. Two different sources of bismuth namely bismuth acetate and bismuth nitrate pentahydrate were used. A solution of bismuth salts were mixed with NH4VO3 solution individually before being titrated against NH4HCO3 solution. The yellowish precipitated formed was calcined at 450oC for 4 hours under air flow. All peaks recorded from XRD pattern, well correspond to monoclinic BiVO4. The FT-IR spectra of the sample powders showed main bands at 800–900 cm-1, assigned as vanadate stretching mode. The scanning electron micrographs showed both BiVO4 were agglomerated with each other due to the smaller surface area. The BET surface area of BiVO4 produced from bismuth nitrate pentahydrate was higher (3.92 m2/g) than that produced from bismuth acetate (2.68 m2/g). Higher surface area (4.29 m2/g) photocatalyst from bismuth nitrate pentahydrate was obtained when calcination temperature reduced to 300oC. It has been applied for photodegradation of MB and RO16 under visible light irradiation. The photodegradation carried out at varying catalyst dosage, dye concentration and pH of the dye. The photodegradation of MB was gradually increased with the increasing of BiVO4 loading up to 0.6 gram with 34% removal while for RO16, the optimum loading was 0.8 gram with 95%. In order to extend the efficiency of photodegradation, prepared BiVO4 was modified by introducing Cu via impregnation method. The mixed solutions of BiVO4 and Cu salt solution were heated at 80oC until all the water evaporated and the calcination process carried out next at 350oC. The same parameters studied for the photodegradation experiments. It showed that 1% Cu-doped BiVO4 gives higher percentage removal of MB and 3% Cu-doped BiVO4 work best for photodegradation of RO16. Both results revealed that the optimum catalyst loading was 0.5 gram with 36 and 100% removal for MB and RO16, respectively. Cu-doped BiVO4 show surface area at 5.76, 4.04 and 4.28 m2/g for 1, 3 and 5% Cu-doped BiVO4,respectively.